The role of Parliament in shaping foreign policy - Nekrašas, Evaldas (Politologija, 1998)
The article deals critically with the doctrine according to which in the process of shaping and implementing foreign policy, the executive branch of the government has many advantages over the legislative and should prevail over it. Foreign policy making in Sweden, United Kingdom, and United States is examined, both on the basis of the results of field research conducted by the author himself and on the findings of other authors. According to the author, the widely made assumption that in all countries foreign policy is almost the exclusive domain of the executive is not correct. In some countries, Parliament plays a relatively important role in this area.The role of the legislature in shaping foreign policy does not substantially depend upon the role a country is playing in world politics or on the content of the policy it pursues. This role depends much more on the character of the political system of that country. The legislature takes a much more active part in foreign policy making in a presidential system than in a parliamentary one. Accordingly, its role is much more important in the United States than in Sweden or the United Kingdom. On the other hand, the legislature is more influential in shaping the future orientation of a country's foreign policy than in current foreign policy making.In the interaction between the executive and legislative branches of government, the legislative process itself is not the focal point. In shaping foreign policy, discussions in the parliamentary committees on foreign affairs and hearings arranged by them are not less but even more important than general debates on the floor of the parliament. Private conversations between MPs and executive officials and contacts between them at various commissions, councils, and delegations have consequences as well.From the adoption of the 1992 Constitution which made Lithuania a semi-presidential republic, its President has formal authority to make the main decisions concerning foreign policy issues. The President's constitutional powers in foreign and domestic policy are unequal: he has little to say on domestic issues but foreign policy is his domain. Yet in practice, foreign policy making has been concentrated recently mainly in the Foreign Ministry and Cabinet chamber. Now both newly elected President Valdas Adamkus and Parliament under the leadership of Vytautas Landsbergis are making attempts to play a much more active role in foreign policy making.
Keywords: -